A Technique for the Measurement of Hot Spots and Isotherm Profiles at the Surfaces of the Elements of Hybrid Microcircuits. (1980) - Sinnadurai, F. N.
Abstract : A simple technique for measuring surface temperatures with high sensitivity and spatial resolution, which is particularly useful for examining temperature distributions of microcircuits, is described. The invention exploits the well-defined "Isotropic-point" transitions of nematic liquid crystals from optical birefringence to anisotropy, using a polarising microscope to detect temperatures in microscopic areas. Thus hot spots appear black against a bright background. The temperature sensitivity is better than 0.5℃ and the spatial resolution better than 5 microns. The technique has distinct advantages over alternative methods of measuring microcircuit temperatures. Examples of applications in support of design evaluation and fault diagnosis of monolithic circuits illustrate the benefits of visual information obtained. The ready application of the technique to the large planar areas of thick film resistors has enabled the location of hot spots – confirming their occurrence at the end of laser cuts – and the measurement of thermal resistances of resistors either singly or in arrays – showing that substantial heat conduction through the substrate can outweigh local non-uniformities in dissipation. Applications extend beyond the supportive role to reliability evaluation illustrated in this paper.